2008
DOI: 10.1186/1756-6606-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Normal mitochondrial respiratory function is essential for spatial remote memory in mice

Abstract: BackgroundMitochondrial DNA (mtDNA) with pathogenic mutations has been found in patients with cognitive disorders. However, little is known about whether pathogenic mtDNA mutations and the resultant mitochondrial respiration deficiencies contribute to the expression of cognitive alterations, such as impairments of learning and memory. To address this point, we used two groups of trans-mitochondrial mice (mito-mice) with heteroplasmy for wild-type and pathogenically deleted (Δ) mtDNA; the "low" group carried 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
(63 reference statements)
4
29
0
Order By: Relevance
“…Thus, the use of mito-mice∆ could provide unambiguous evidence that pathological phenotypes exclusively observed in mito-mice∆ carrying high loads of ∆mtDNA are caused by ∆mtDNA-induced mitochondrial respiration defects. Our experiments clearly showed that loads of 50% or less ∆mtDNA did not induce mitochondrial respiration deficiencies in the brain tissues and were also not associated with behavioral abnormalities, whereas loads of more than 60% were able to induce mitochondrial respiration defects and downregulation of CaM kinase II subunit alpha in brain tissues, leading to impairment of spatial remote memory [41].…”
Section: Abnormalities Of Spatial Remote Memory In Mito-mice∆mentioning
confidence: 61%
See 3 more Smart Citations
“…Thus, the use of mito-mice∆ could provide unambiguous evidence that pathological phenotypes exclusively observed in mito-mice∆ carrying high loads of ∆mtDNA are caused by ∆mtDNA-induced mitochondrial respiration defects. Our experiments clearly showed that loads of 50% or less ∆mtDNA did not induce mitochondrial respiration deficiencies in the brain tissues and were also not associated with behavioral abnormalities, whereas loads of more than 60% were able to induce mitochondrial respiration defects and downregulation of CaM kinase II subunit alpha in brain tissues, leading to impairment of spatial remote memory [41].…”
Section: Abnormalities Of Spatial Remote Memory In Mito-mice∆mentioning
confidence: 61%
“…On the basis of our findings, we suggest that some cases of human memory defect are caused by high loads of pathogenic mutant mtDNA and the resultant mitochondrial respiration defects [41]. We also suggest that improving mitochondrial respiration and/or location of CaM kinase II subunit alpha might be effective strategies for treating memory disorders, although there are biological differences between such disorders in humans and mice.…”
Section: Abnormalities Of Spatial Remote Memory In Mito-mice∆mentioning
confidence: 63%
See 2 more Smart Citations
“…Collectively, this pattern is highly reminiscent of human mitochondrial spongiform encephalopathies, particularly of KSS and, in some aspects, LS (Table 2) ERRγ [123], NRF-1 [124], NRF-2 [125], Tfam [126], mtDNA polymerase γ 1 (POLG1) [127], optic atrophy 1 (OPA1) [128] and synthesis of cytochrome c oxidase 2 (SCO2) [129]), whereas a great proportion of viable strains, surprisingly, exhibit no neuropathology (e.g., knockouts of ANT-1 [130], PPARγ [131], ERRα [132], and SURF1 [133]; Twinkle mutant 'Deletor' mice [134], and ΔmtDNA Mito-Mice [135]). To our knowledge, murine knockouts of AIF [136,137], SOD2 [138], thymidine phosphorylase and uridine phosphorylase (TP/UP) [139], and NADH dehydrogenase [ubiquinone] iron-sulfur protein 4 (NDUFS4) [140] are the only ones that display a neuropathology resembling that of human mitochondrial encephalopathies (Table 2).…”
Section: Figure 15 Distinct Types Of Intramyelin Vacuoles In Kssmentioning
confidence: 99%